2013
DOI: 10.1590/s0101-20612013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and development of marolo (Annona crassiflora, Mart.)

Abstract: The objectives of this study was the physical, chemical, and physiological characterization of marolo (Annona crassiflora, Mart.) during its development. The fruits were harvested 12 Km off Itumirim, Southern Minas Gerais, Brazil, at 20-d intervals from anthesis to fruit maturity. The first fruits were harvested within 60 days. The total development of the fruit took 140 days starting from anthesis. At 140 days after anthesis, the fruit reached its maximum size, with mass of 1.380g, transverse diameter of 13.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
(21 reference statements)
1
7
1
1
Order By: Relevance
“…Marolo has previously shown mainly oxygenated sesquiterpenes (SIRENA et al, 2014). However, in this study, ripe fruit pulp extracted by SPME showed only esters, mainly methyl and ethyl derivatives of hexanoate, octanoate and decanoate (SILVA et al, 2013). Terpenes were also identified, but only in the stages prior to full fruit ripening.…”
Section: Resultscontrasting
confidence: 64%
“…Marolo has previously shown mainly oxygenated sesquiterpenes (SIRENA et al, 2014). However, in this study, ripe fruit pulp extracted by SPME showed only esters, mainly methyl and ethyl derivatives of hexanoate, octanoate and decanoate (SILVA et al, 2013). Terpenes were also identified, but only in the stages prior to full fruit ripening.…”
Section: Resultscontrasting
confidence: 64%
“…The degradation and synthesis of new volatile compounds occur through the end of the physiological process. Silva et al (2013) reports that volatile compounds are of great importance during the development process, because they facilitate the maintenance and perpetuation of the species. These compounds are responsible for the characteristic aroma and can be synthesized during development, post-harvest, and storage.…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional and commercial potential knowledge of the native species could be an economic alternative to the livelihood of native population from different regions (Silva et al, 2013). Fruits and vegetables are important examples of essential elements source.…”
Section: Introductionmentioning
confidence: 99%